Previsões para o ICMS no Ceará: comparação do desempenho da metodologia da SEFAZ-CE com o modelo ARIMA - Rocha Neto, Augusto (2009)
This research aims to offer managers of the State of Ceará a choice of tool to perform estimates of the monthly tax collection Movement of Goods and Services (ICMS), exemplifying the procedures carried out for the period September 2007 to January 2008, through an econometric model consistent with a good predictive power. For this, use is known as univariate ARIMA model, with the use of seasonal dummy, which are very efficient to perform forecasts. The forecasts generated by the research confirms the ability of ARIMA models to forecast opportunity, given the small margin of error, and yet, in view of a comparison between the predictions made by the SEFAZ-CE with those produced by the search, you can say that the model used here is more accurate than the method employed by the Department of Finance to provide for collection of ICMS in Ceará.